Analysis Of Factors Affecting Price Movements Indonesia Stock Exchange Industrial Classification: English - Muhammad Wahyu Akbar; Sri Mulatsih; Sahara Sahara (Agregat: Jurnal Ekonomi dan Bisnis, 2023)
This study aims to analyze the impact of movements in exchange rates, world gold price, world crude oil price and Covid-19 cases on Indonesia Stock Exchange Industrial Classification (IDX-IC). This study uses Vector Autoregression/ Vector Error Correction Model with daily data from January 26, 2021, to April 28, 2022. The results of this study show that exchange rate has a positive effect on industrial, transportation and logistics sector. Then, world gold price has a negative effect on several sectors, namely energy, industry, health and finance. Covid-19 case has a negative effect on transportation and logistics sector. The impulse response function test results show that each sector responded differently to shocks to exchange rates, world gold prices, world crude oil prices and Covid-19 cases. However, all sectors responded to these shocks in the second period and returned to a stable point in the fifth. The results of forecast error variance decomposition test show that the sectoral stock price index contributes the most for itself, followed by world gold prices, exchange rates, Covid-19 cases and world crude oil prices.